ChemInform Abstract: Stereoselective Synthesis of 1‐Methyl‐3′, 4′, 5′, 6′‐tetrahydrospiro[indoline‐3, 2′‐pyran]‐2‐one Derivatives via Prins Cyclization. Issue 41 (October 2015) - Damera, Krishna; Yu, Bingchen; Wang, Binghe
Abstract Spirooxindole alcohols (III) and fluorides (IV) are readily prepared as single diastereomers by a Lewis acid promoted Prins cyclization of 3‐allyl‐3‐hydroxy indolinones (I) with aldehydes (II).